2023
DOI: 10.3389/fsurg.2022.1069709
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, prognostic potency, and longitudinal variation of anxiety and depression in postoperative glioma patients

Abstract: ObjectiveAnxiety and depression are common mental disorders in glioma patients. This study aimed to evaluate the risk factors, prognostic role, and longitudinal changes in anxiety and depression in postoperative glioma patients.MethodsAnxiety and depression were assessed by Hospital Anxiety and Depression Scale at baseline, month (M) 6, M12, M24 and M36 in 270 glioma patients after surgical resection. Furthermore, comprehensive clinic characteristics and treatment-related information were collected.ResultsGend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In addition, a study in 2022 proved that both depressive disorders, but also gender, WHO classification, prognosis and being married, partnered also affected the worsening of survival in glioma patients. [12] Patients with such disorders should be put on special protocols that include antidepressant treatments, psychotherapy. Unfortunately, we do not have such standards in the world, and the diagnosis of psychopathological disorders in people with CNS tumors is often overlooked due to the focus of attention and treatment directed at the underlying disease.…”
Section: Effect Of Depression and Its Treatment On Survival Of Patien...mentioning
confidence: 99%
“…In addition, a study in 2022 proved that both depressive disorders, but also gender, WHO classification, prognosis and being married, partnered also affected the worsening of survival in glioma patients. [12] Patients with such disorders should be put on special protocols that include antidepressant treatments, psychotherapy. Unfortunately, we do not have such standards in the world, and the diagnosis of psychopathological disorders in people with CNS tumors is often overlooked due to the focus of attention and treatment directed at the underlying disease.…”
Section: Effect Of Depression and Its Treatment On Survival Of Patien...mentioning
confidence: 99%
“…In addition, a study in 2022 proved that both depressive disorders, but also gender, WHO classification, prognosis and being married, partnered also affected the worsening of survival in glioma patients. [12] Patients with such disorders should be put on special protocols that include antidepressant treatments, psychotherapy. Unfortunately, we do not have such standards in the world, and the diagnosis of psychopathological disorders in people with CNS tumors is often overlooked due to the focus of attention and treatment directed at the underlying disease.…”
Section: Effect Of Depression and Its Treatment On Survival Of Patien...mentioning
confidence: 99%
“…Compared to HGG group without depression, HGG patients with depression have shorter overall survival. [ 11 22 23 24 ] In contrast, Arja et al [ 25 ] found that patients with preoperative depression had significantly shorter survival time than non-depressed patients in a subgroup of patients with LGG. However, they did not find this phenomenon in patients with HGG.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The worldwide median survival time for patients with lowgrade glioma (LGG) is 5.6-13.3 years and for patients with high-grade glioma (HGG), it is only 12.2-15.4 months. [11][12][13] Stress is a regular part of daily life. Stress responses can have various effects on the body, and when the duration of the stressor is limited, it gives people an experience of excitement and accomplishment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation